PENDAMPINGAN TENANT UMKM JUS KEDONDONG JUSDOONG DALAM PROGRAM INKUBASI BISNIS KABUPATEN TANGERANG - Matiini, Gharizi (Universitas Mataram, 2025)
The Covid-19 Pandemic hitting the world since 2020 has greatly affected the economic movement of MSME’s in Indonesia. Many small businesses have reduced their production and even some of them had to go out of business due to the declining market demand and high prices of production materials. MSME’s in Kedondong Juice business are also among those whose demands have decreased drastically since the Pandemic hit in Indonesia. The decreasing market demands and the high price of Kedondong fruit are the reasons why this business is not as famous as before. The aim of this community service is to provide assistance and mentoring to Kedondong Juice MSMA business, in order to increase the number of sale and expand the market share. This MSME assistances include mentoring, supervision, outreach and assistance activities as part of the efforts to supports MSME group and to overcome problems face by MSME communities. The assistance methods consist of discussions, seminar participation, regular monitoring, and providing administrative and legal assistance to Kedondong Juice MSME tenant. The results of this community service show that Kedondong Juice business needs to widen the product sales and marketing area, register the product’s Intellectual Property Rights (HKI) and they can sell the product in minimarkets and supermarkets, and optimize online sales through Online Market Place. The final results of this mentoring are the IPR registration and the increase sales in online Market Place.